International Economics - Pugel, Thomas A (Mc Graw Hill Higher Education, 2020)
International Economics is Different; The Basic theory using demand and supply; Why Everybody trade: Comparative Advantage; Trade: Factor Availability and Pactor Proportions Are Key ....